Iktiofauna ekosistem estuari Mayangan, Jawa Barat [Ichthyofauna of Mayangan estuary, West Java] - Ahmad Zahid; Charles P.H. Simanjuntak; M. F. Rahardjo; Sulistiono Sulistiono (Jurnal Iktiologi Indonesia, 2011)
Estuaries areas are the complex ecosystem and provide habitat for aquatic organisms, particularly for fishes. A study was conducted to determine fish species diversity in Mayangan estuary, from December 2010 to May 2011. Sampling was conducted in the three zones, namely marine coastal, river mouth, and mangrove creek. Fish specimens were collected by gill net, trammel net, beach seine, and mini trawl. A total of 2,854 fishes consisted of 46 families and 105 species, and the most collected group of fish was Carangidae. Based on occupied habitat, the richest number of species was found in the marine coastal (61), followed by the river mouth (16), and mangrove creeks (1). Typically marine-estuarine and estuarine-freshwater forms were represented by 15 and 12 species, respectively. The presence of fish larvae and juvenile in species composition indicated that Mayangan estuary has the function as habitat for feeding, spawning, refuge, and nursery. AbstrakEstuari adalah ekosistem yang kompleks dan menyediakan habitat bagi beragam biota akuatik, khsususnya ikan. Penelitian dilakukan pada bulan Desember 2010 hingga Mei 2011 untuk menentukan keragaman spesies ikan di estuari Mayangan. Pengambilan contoh dilakukan di tiga zona, yaitu pantai terbuka, muara sungai, dan alur sungai berhutan mangrove (anak sungai). Spesimen ikan dikumpulkan dengan jaring rampus dan jaring blama (gill net), jaring belanak (trammel net), krakat (beach seine), dan jaring arad (mini trawl). Ikan yang terkumpul sebanyak 2.854 ekor yang terdiri atas 46 famili dan 105 spesies, dan famili dominan adalah Carangidae. Berdasarkan habitat yang didiami, spesies terbanyak ditemukan di pantai terbuka sebanyak 61 spesies, 16 spesies ditemukan di mulut sungai, 1 spesies di alur sungai berhutan mangrove. Ikan bertipe habitat di pantai terbuka dan muara sungai berjumlah 15 spesies, sedangkan di muara sungai dan anak sungai diwakili oleh 12 spesies. Keberadaan larva dan juwana ikan di estuari Mayangan sebagai bagian dari komposisi spesies menunjukkan peran fungsional estuari sebagai daerah pemijahan, pembesaran, perlindungan, dan lumbung makanan.